Low-Profile Wideband Antenna Arrays for Mobile Satellite and 5G Communication - BENJAMIN FALKNER (2023)
Three innovative low-profile antenna arrays are designed and tested for vehicular satellite and 5G communication. All of the systems presented target key challenges of GEO, LEO and 5G communication. Each design provides a high level of performance for the given application in a far more compact and lower cost design than existing systems.Firstly, a wideband curl antenna array is developed to enable L-band GEO satellite communication for emergency vehicles. This novel 1×3 rotated array utilises a hybrid switch beam and phase shifting technique to enable full beamforming down to 70° in all directions with 40% lower cost than standard phased array systems. Uniquely, this provides excellent azimuth beam steering at low angles from a linear array. This system also utilises a high impedance surface to reduce the height of the antenna elements by 50% compared to existing curl antenna designs.Secondly, a shared aperture antenna array is developed to enable Ka-band LEO satellite communication for vehicular integration. This system utilise a new combination of circular polarised triangular antennas in an interlaced planar triangular lattice such that the topology provides optimal tessellation. As a result, the system provides high performance beam steering and reconfigurable circular polarisation in a highly compact design. This array has been developed such that it is suitable for common PCB manufacturing methods. Unlike existing shared aperture arrays for LEO terminals, this topology enables reconfigurable circular polarisation in a single, planar PCB structure.Finally, a low-cost wideband compressed spiral antenna array is designed and fabricated for global 5G ground-to-air communication for aircraft. An innovative spiral antenna optimisation is presented where the spiral is highly compressed such that it can provide an axial beam over a wide bandwidth while maintaining a lower profile than existing wideband solutions.